2020
DOI: 10.31254/dentistry.2020.5211
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of malocclusion and occlusal traits of Malay adults (18-23 years) in Shah Alam, Malaysia

Abstract: Background: The incidence of malocclusion varies among countries, ethnicities, races, and ages. The recognition of malocclusion incidence is an important role in planning public health services. Aims: To assess the occlusal features of Malaysian Malay adults aged 18-23 years. However, few epidemiological studies have been conducted in Malaysia and a little information is available on Malay malocclusion. Methods: A total sample of 191 subjects (73 males and 118 females) was examined to register the occlusal sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Hence, the hypothesis that no significant association existed between the prevalence of skeletal patterns and gender was rejected. It was in agreement with the literature that the Malay male subjects were more likely to have Class III malocclusion than their female counterpart (8). Sexual dimorphism and growth in the mandible between males and females could be accounted for the difference observed (23,24).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Hence, the hypothesis that no significant association existed between the prevalence of skeletal patterns and gender was rejected. It was in agreement with the literature that the Malay male subjects were more likely to have Class III malocclusion than their female counterpart (8). Sexual dimorphism and growth in the mandible between males and females could be accounted for the difference observed (23,24).…”
Section: Discussionsupporting
confidence: 90%
“…In this study, the prevalence of Class I skeletal pattern was 41.3%, Class II: 46.1%, and Class III: 12.6%. Based on the literature reviews, the prevalence of Class I malocclusion in the Malay population was reported to be in the range of 33.3% to 39.3%, Class II: 12% to 30%, and Class III: 12.2% to 48.7% (6)(7)(8). The large variation between different studies was due to different sampling methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 20 ] Class III malocclusion was found to be most common in adult males (67.1%) and adult females (37.3%) in the Malaysian population. [ 21 ] It has been reported that the prevalence of clinically significant malocclusion among adults in the United States is greater than 60%. [ 22 ] Hence, there is a need for correction of malocclusion.…”
Section: Discussionmentioning
confidence: 99%